Implementasi Fuzzy Inference System Mamdani Pada Proses Penentuan Kelulusan Calon Mahasiswa (Studi Kasus : Penerimaan Mahasiswa Baru Politeknik Negeri Lhokseumawe Jalur UMPN) - Rahmad Hidayat (Teknik Informatika Universitas Malikussaleh, 2015)
Admissions is an important process in a college. To get the best candidate as the input for each faculities is quite complex, which is linked to few criteria that must be fullfill. At The State Polytechnic Of Lhokseumawe there are several paths in attracting prospective students, which are Bidik Misi, Undangan and UMPN. This study focuses only on new admissions to the track UMPN. The criteria used to determine graduation students in this study include entrance exam scores, UAN and and average report card on the semester 4,5 and 6. Each of these criteria will be used as the input set on Mamdani Fuzzy Inference. Input value entrance exam has three categories: low, medium and high. While the value of UAN has a set of categories, low, medium and high. The third input is the average rapot semester 4,5, and 6 have the categories of low, medium and high. The next step in mapping the set of input to output sets using the set of rules. The results obtained in this study is a prospective student fails to 33.33%, while 21.4% passed the reserves, and 48.77% passed.